Novel ultrasound contrast agent dilution method for the assessment of ventricular ejection fraction. - Jansen A; Mischi M; Bracke F; van Dantzig JM; Peels K; Lamfers E; van Hemel N; Korsten H (European Journal of Echocardiography, 2008)
AIMS: Left ventricular (LV) ejection fraction is an important determinant of prognosis in heart failure. We evaluated the accuracy of a novel algorithm for LV ejection fraction quantification based on indicator dilution curve (IDC) principles using ultrasound contrast as indicator, and compared the results with contrast enhanced biplane LV ejection fraction assessment. Method A diluted ultrasound contrast bolus (SonoVue) was injected intravenously in 31 patients (19 male, age 65 +/- 11) with known or suspected heart disease. A total of 68 recordings were made. The developed algorithm used the left atrium and LV IDC for LV ejection fraction measurement. Biplane enhanced LV ejection fraction measurements with pure ultrasound contrast (SonoVue) were determined in multiple four- and two-chamber recordings as reference. RESULTS: The mean LV ejection fraction measured by biplane and IDC method was 33 +/- 17% and 35 +/- 18%, respectively. A correlation coefficient r = 0.93 was observed between the two methods. Bland-Altman analysis demonstrated a slight LV ejection fraction overestimation with IDC (mean 1.9 +/- 6.3%). CONCLUSION: A new fast method for LV ejection fraction assessment based on IDC principles is described and comparison with contrast enhanced biplane LV ejection fraction quantification shows accurate results.